Serum hyaluronic acid, a marker for improved liver perfusion after gradual surgical attenuation of extrahepatic portosystemic shunt closure in dogs. (February 2021) - Devriendt, N.; Serrano, G.; Meyer, E.; Demeyere, K.; Paepe, D.; Vandermeulen, E.; Stock, E.; de Rooster, H.
Highlights: Serum hyaluronic acid (sHA) has potential as a marker of liver perfusion in dogs. sHA was increased in most dogs with extrahepatic portosystemic shunts (EHPSS). Median sHA significantly decreased after surgery for EHPSS. sHA was significantly lower with closed EHPSS than with persistently shunting. Abstract: Current liver function tests used in dogs do not consistently normalise after successful surgical attenuation of portosystemic shunts (PSS). Serum hyaluronic acid (sHA) concentrations in dogs with PSS are reported to be higher at diagnosis than in healthy dogs. The objective of this study was to assess sHA as a marker of liver perfusion by measuring sHA concentrations in dogs before and after gradual surgical attenuation of extrahepatic (EH)PSS and by determining whether sHA concentrations could differentiate closed EHPSS from persistent shunting. Specificity of sHA was assessed by comparing sHA concentrations in dogs with EHPSS to those in dogs with other liver diseases. Twenty dogs with EHPSS had sHA concentrations measured at diagnosis, 1, 3, and 6 months postoperatively. In addition, sHA concentrations were determined in 10 dogs with other liver diseases. At EHPSS diagnosis, median sHA concentration was 335.6 ng/mL (43.0−790.7 ng/mL). All dogs had a significant decrease in sHA concentrations from 1 month postoperatively onwards (P < 0.05), regardless of surgical outcome. At all postoperative follow-up visits, there was a significant difference between the median sHA concentration in dogs with closed EHPSS vs. those with persistent shunting (P < 0.05). Median sHA concentration in dogs with other liver diseases was 89.8 ng/mL (22.9−160.0 ng/mL), which was significantly lower than dogs with EHPSS at diagnosis (P < 0.001). In conclusion, sHA is a promising non-invasive biomarker that can help to determine liver perfusion after surgical attenuation of EHPSS. In addition, sHA could potentially be used to differentiate dogs with EHPSS from dogs with other liver diseases.